Are complement deficiencies really rare?: overview on prevalence, clinical importance and modern diagnostic approach - Grumach, Anete; Kirschfink, Michael (Molecular immunology, 2014)
Complement deficiencies comprise between 1 and 10% of all primary immunodeficiencies (PIDs) according to national and supranational registries. They are still considered rare and even of less clinical importance. This not only reflects (as in all PIDs) a great lack of awareness among clinicians and general practitioners but is also due to the fact that only few centers worldwide provide a comprehensive laboratory complement analysis. To enable early identification, our aim is to present warning signs for complement deficiencies and recommendations for diagnostic approach. The genetic deficiency of any early component of the classical pathway (C1q, C1r/s, C2, C4) is often associated with autoimmune diseases whereas individuals, deficient of properdin or of the terminal pathway components (C5 to C9), are highly susceptible to meningococcal disease. Deficiency of C1 Inhibitor (hereditary angioedema, HAE) results in episodic angioedema, which in a considerable number of patients with identical symptoms also occurs in factor XII mutations. New clinical entities are now reported indicating disease association with partial complement defects or even certain polymorphisms (factor H, MBL, MASPs). Mutations affecting the regulators factor H, factor I, or CD46 and of C3 and factor B leading to severe dysregulation of the alternative pathway have been associated with renal disorders, such as atypical hemolytic uremic syndrome (aHUS) and - less frequent - with membranoproliferative glomerulonephritis (MPGN). We suggest a multi-stage diagnostic protocol starting based on the recognition of so called warning signs which should aid pediatricians and adult physicians in a timely identification followed by a step-wise complement analysis to characterize the defect at functional, protein and molecular level.